Pengembangan Video Pembelajaran Fisika Berbantuan Animasi Drawing Sparkol Videoscribe Berorientasi Pada Kemampuan Analisis Peserta Didik - Roni Roni; Syarif Fitriyanto; Hermansyah Hermansyah; Fahmi Yahya; Suji Adrianti (Journal of Science Instruction and Technology, 2021)
The learning process so far has only been based on textbooks. In addition, teachers still use minimal media in learning so it has an impact on the low analytical ability of students. This study aims to determine 1). The feasibility level of learning videos assisted by the Drawing Sparkol Videoscribe animation developed by researchers, 2) Student responses to learning videos. This study uses the Research and Development (R&D) model. The model uses Robert Maribe Branch's version of ADDIE. The instrument used is a questionnaire. Product validation is carried out by media experts, material experts and has been tested in class XI IPA as many as 10 students. The results showed that the development of physics learning videos assisted by the Drawing Sparkol Videoscribe animation was very feasible to be used as a learning medium. Feasibility is shown based on the assessment of material experts getting an average percentage value of 96.36% including in the very feasible category, media expert assessment getting an average percentage value of 91.76% including in the very feasible category, and the assessment of student responses getting an average value the percentage of 87.06% is included in the very good category used in learning.